A light-entrainment mechanism for the Drosophila circadian clock. - Zeng, H.; Qian, Z.; Myers, M.P.; Rosbash, M. (Nature, 1996)
Biochemical studies indicate that the Drosophila timeless protein (Tim) is a stoichiometric partner of the period protein (Per) in fly head extracts. A Per-Tim heterodimeric complex explains the reciprocal autoregulation of the proteins on transcription. The complex is under clock control, and many circadian features of the Tim cycle resemble those of the Per cycle. However, Tim is rapidly degraded in the early morning or in response to light, releasing Per from the complex. The Per-Tim complex is a functional unit of the Drosophila circadian clock, and Tim degradation may be the initial response of the clock to light.